Anti-Müllerian hormone as an indicator of reproductive health in women with obesity and concomitant polycystic ovary syndrome - Durmanova, A K; Otarbaev, N K (Terapevtic̆eskii arhiv, 2016)
To investigate the ovarian reserve and a relationship between the level of anti-Müllerian hormone (AMH) with that of hormones in reproductive-aged women with abdominal obesity concurrent with and without polycystic ovary syndrome (PCOS). A total of 157 women aged 18 to 45 years with a body mass index (BMI) of more than 30 kg/m2 were examined. The 157 women with abdominal obesity were conventionally divided into 2 groups: 1) 20 with PCOS and 2) 137 without this condition. Morphometric parameters, the indicators of carbohydrate and lipid metabolism, and the levels of hormones, including AMH, were studied. The patients with PCOS had statistically significantly elevated AMH levels (11.26±2.63 ng/ml; p<0.0001). The group of obese patients without PCOS showed a negative correlation of the levels of AMH with those of follicle-stimulating hormone (FSH) (p=0.0004), luteinizing hormone (LH) (p=0.0171), and HOMA-IR (p=0.0572). In reproductive-aged women with abdominal obesity without concomitant PCOS in the presence of insulin resistance, the ovarian reserve decreases and the levels of FSH and LH increase, which leads to accelerated aging processes in the reproductive system. In this case, the patients with PCOS display a significant increase in the AMH levels; therefore, their determination can be used in the algorithm for diagnosing PCOS.